NK Cell Subsets Changes in Partial Remission and Early Stages of Pediatric Type 1 Diabetes - Gomez-Muñoz, Laia; Perna-Barrull, David; Villalba, Adrian; Rodriguez-Fernandez, Silvia; Ampudia, Rosa-Maria; Teniente-Serra, Aina; Vazquez, Federico; Murillo, Marta; Perez, Jacobo; Corripio, Raquel; Bel, Joan; Vives-Pi, Marta (Frontiers in Immunology, 2021)
Type 1 diabetes (T1D) is a chronic metabolic disease characterized by the autoimmune destruction of β-cells in the pancreatic islets. T1D is preceded by islet-specific inflammation led by several immune cells. Among them, natural killer (NK) cells are emerging as important players in T1D development. Human NK cells are characterized by CD56 and CD16 expression, which allows classifying NK cells into four subsets: 1) CD56dimCD16+ or NK effector cells (NKeff); 2) CD56brightCD16- or regulatory NK cells (NKreg); 3) intermediate CD56brightCD16+ NK cells; and 4) CD56dimCD16- NK cells, whose function is not well determined. Since many studies have shown that T1D progression is associated with changes in various immune cell types, we hypothesize that the kinetics of NK cell subsets in the blood could correlate with different stages of T1D. To that aim, pediatric patients newly diagnosed with T1D were recruited, and peripheral NK cell subsets were analyzed by flow cytometry at several disease checkpoints: disease onset, partial remission (PR), 8 months (for non-remitters), and 12 months of progression. Our results showed that total NK cells and their four subsets are altered at the early stages of T1D. A decrease in the counts and percentage of total NK cells and NKeff cells at the different disease stages was found when compared to controls. These results suggest the extravasation of these cells into the islets at disease onset, which is maintained throughout the follow-up. By contrast, NKreg cells increased during the early stages after T1D onset, and both intermediate NK cells and CD56dimCD16- NK cells diminished at the PR stage, which might reflect the immunoregulatory attempts and could be candidate biomarkers for this stage. Also, CD56dimCD16- NK cells increased during T1D progression. Finally, changes in CD16 expression were identified in the different T1D stages, highlighting a CD16 expression reduction in total NK cells and NKeff cells one year after diagnosis. That may reflect a state of exhaustion after multiple cell-to-cell interactions. Altogether, our preliminary data provide a longitudinal picture of peripheral NK cell subpopulations during the different T1D stages, which could be potential candidate biomarkers indicators of disease progression.